TINDAK TUTUR ILOKUSI PADA IKLAN MATAHARI: FEEL GOOD KETIKA KITA SALING MELENGKAPI - aini, Nur (University of Brawijaya, 2023)
Language expressions from time to time are increasingly used in various industrial fields, one of which is used in advertising speech on Youtube media. The use of speech in advertising is often used for media promotion to consumers. The utterances in advertisements are not only ordinary utterances that are spoken, one of the speech acts is found, namely illocutionary speech acts. This study was made with the aim of describing the forms of illocutionary speech acts contained in advertisements and describing the types of speech acts either directly or indirectly in the video Matahari: Feel Good When We Complete Each Other. This study classifies the illocutionary speech acts in the video as processed data. Researchers used qualitative-descriptive research methods. The technique used is the free-of-conversation listening technique. After being listened to, the source of the data obtained is recorded and classified based on the type and form of speech. The data obtained show that, the types of illocutionary speech acts in the advertisement are Assertive speech acts with a total of 2 utterances that read the same, Expressive with 4 utterances with 3 utterances of gratitude and the rest congratulating, and Directive speech acts with a total of 3 utterances. , while commissive and declarative speech acts were not found. Meanwhile, the form of direct speech found is 7 utterances and indirect speech is 1 utterance which belongs to the directive question speech act. Based on the results of these data, expressive and directive illocutionary speech acts are fairly dominant compared to the others. The form of direct speech also dominates the speech, this indicates that the speech delivered is made so that the speech partner easily understands the meaning conveyed by the speaker.